Book review. Horsti, Karina. Survival and Witness at Europe’s Border: The Afterlives of a Disaster. : Ithaca and London: Cornell University Press. 2023. - Seuferling, Philipp (MedieKultur: Journal of media and communication research, 2024)
n/a